(untitled) (Universal International Scientific Journal, 2026)
This report provides a comprehensive analysis of the legal framework, institutional mechanisms, and organizational and economic means for implementing scientific research results in the Republic of Uzbekistan. The processes of commercialization of scientific results, protection of intellectual property, and technology transfer are covered on the basis of regulatory legal acts regulating science and innovative activities, in particular, the Constitution of the Republic of Uzbekistan, the Law on Science and Scientific Activity, and the Law on Innovative Activities.